2014
DOI: 10.1126/science.1243339
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Life Span and Physiology Are Modulated by Sexual Perception and Reward

Abstract: Sensory perception modulates aging and physiology across taxa. We found that perception of female sexual pheromones through a specific gustatory receptor expressed in a subset of foreleg neurons in male fruit flies, Drosophila melanogaster, rapidly and reversibly decreases fat stores, reduces resistance to starvation, and limits lifespan together with neurons that express the reward-mediating neuropeptide F. High-throughput RNA-seq experiments revealed a set of molecular processes that were impacted by the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
165
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(186 citation statements)
references
References 27 publications
14
165
4
Order By: Relevance
“…In Antechinus marsupial mice, synchronous polyandry by females drives intense post-copulatory sexual selection in males, leading to the death of the males within the breeding season [12]. More recently, longevity effects associated with continued mate-seeking behaviour have been observed in Drosophila melanogaster [13]. Males maintained in the presence of female pheromones, but in the absence of a mate, died before males that were sexually satiated or maintained without the stimulus to seek mates.…”
Section: Introductionmentioning
confidence: 99%
“…In Antechinus marsupial mice, synchronous polyandry by females drives intense post-copulatory sexual selection in males, leading to the death of the males within the breeding season [12]. More recently, longevity effects associated with continued mate-seeking behaviour have been observed in Drosophila melanogaster [13]. Males maintained in the presence of female pheromones, but in the absence of a mate, died before males that were sexually satiated or maintained without the stimulus to seek mates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been found that exposure to pheromones can adversely affect lifespan (Gendron et al 2014). Decreased fat stores, reduced resistance to starvation and a reduced lifespan were observed in male Drosophila melanogaster (Meigen, 1830) exposed to female sex pheromones (Gendron et al 2014). Although these effects were reversed by mating (Gendron et al 2014); the possible impacts on lifespan should be considered when proposing to expose insects of conservation value to pheromones.…”
Section: Figure 3 4 Discussionmentioning
confidence: 99%
“…This increased vulnerability to predation could prove damaging to populations being monitored using pheromones. Recently it has been found that exposure to pheromones can adversely affect lifespan (Gendron et al 2014). Decreased fat stores, reduced resistance to starvation and a reduced lifespan were observed in male Drosophila melanogaster (Meigen, 1830) exposed to female sex pheromones (Gendron et al 2014).…”
Section: Figure 3 4 Discussionmentioning
confidence: 99%
“…To the Editor -In a recent issue of Nature Ecology and Evolution, Harvanek et al show that male fruit flies (Drosophila melanogaster) experience key survival and physiological costs as a sole consequence of perceiving female pheromones 1,2 . This is an outstanding example of how sensory perception can drastically modulate ageing through different pathways 1,[3][4][5] , presumably by engaging physiological responses evolved to deal with environmental challenges that, in nature, would normally be associated with the perceived stimuli.…”
Section: Perception Costs Of Reproduction Can Magnify Sexual Selectionmentioning
confidence: 99%
“…This is an outstanding example of how sensory perception can drastically modulate ageing through different pathways 1,[3][4][5] , presumably by engaging physiological responses evolved to deal with environmental challenges that, in nature, would normally be associated with the perceived stimuli. Crucially, Harvanek et al show that perception costs of reproduction by exposure to sexual pheromones mostly disappear when male flies have access to regular matings, suggesting that perception of sexual pheromones triggers physiological changes that only result in accelerated ageing when uncoupled with the mating expectations it generates 1,2 .…”
Section: Perception Costs Of Reproduction Can Magnify Sexual Selectionmentioning
confidence: 99%